2014
DOI: 10.1111/evj.12307
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteraemia and host response in healthy neonatal foals

Abstract: Positive blood cultures suggest transient bacteraemia may occur in healthy foals early in the post natal period. Age corrected normal values may be necessary to interpret cytokine concentration in diseased populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 29 publications
(36 reference statements)
1
49
5
Order By: Relevance
“…Some of these factors, such as temperature and neutrophils were significantly associated with both nonsurvival and natural death in the current study. Despite the recent finding that bacteria are intermittently detected in the blood of some apparently healthy foals [19], the current study demonstrates that bacteraemia is strongly associated with both nonsurvival and natural death. Several studies have documented an association between admission lactate concentration and outcome in equine neonates [5,18].…”
Section: Discussioncontrasting
confidence: 99%
“…Some of these factors, such as temperature and neutrophils were significantly associated with both nonsurvival and natural death in the current study. Despite the recent finding that bacteria are intermittently detected in the blood of some apparently healthy foals [19], the current study demonstrates that bacteraemia is strongly associated with both nonsurvival and natural death. Several studies have documented an association between admission lactate concentration and outcome in equine neonates [5,18].…”
Section: Discussioncontrasting
confidence: 99%
“…Better diagnostic methods to identify bacteremia are necessary to improve the quality of such research. Additionally, consideration of the fact that some healthy neonatal foals are bacteremic, but not septic, should be given . Although it is unlikely that the septic foals in our study were falsely identified as septic (ie, positive blood culture but sick‐nonseptic or healthy) because all foals were admitted to referral hospitals and were considered sick, it is possible that some merely had transient bacteremia with no adverse consequences.…”
Section: Discussionmentioning
confidence: 98%
“…However, blood culture techniques have several limitations including temporal delay in result reporting (48–72 hours), low chance of isolation of some pathogens and only fair sensitivity . Furthermore, positive blood cultures have been documented in healthy neonatal foals or can be positive in association with other disease processes that allow bacterial translocation, both of which might cause transient bacteremia, but not reflect true infection . False negative blood culture results also might occur from low numbers of circulating bacteria, collection of low volumes of blood for culture, and prior antimicrobial administration .…”
Section: Introductionmentioning
confidence: 99%
“…2008), a primary presenting complaint in 115 of the foals of the current study, where 66 foals were bacteraemic at admission and no association of bacteraemia with survival was found. One recent study (Hackett et al . 2010) reported that normal foals repeatedly sampled over the first 72 h of life were commonly blood culture positive on at least one sample; all positive cultures were obtained under age 12 h and no foal was clinically ill at any point during or following the study.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association of blood culture status with outcome has already been questioned in 133 neonatal foals with diarrhoea (Hollis et al 2008), a primary presenting complaint in 115 of the foals of the current study, where 66 foals were bacteraemic at admission and no association of bacteraemia with survival was found. One recent study (Hackett et al 2010) reported that normal foals repeatedly sampled over the first 72 h of life were commonly blood culture positive on at least one sample; all positive cultures were obtained under age 12 h and no foal was clinically ill at any point during or following the study. Although only a small number of foals (7) were studied, the results do call into question the common use of blood culture as a method of determination of 'septic vs. not septic' in equine neonates, as bacteraemia may be relatively common in the first few days of life in apparently clinically normal foals.…”
Section: Discussionmentioning
confidence: 99%